2016
DOI: 10.1017/s0025315416000229
|View full text |Cite
|
Sign up to set email alerts
|

Changes in macrobenthic community structure from estuary to continental slope in the south-east coast of India

Abstract: The pattern of changes in the macrobenthic community was studied along the south-east coast of India from the estuary to continental slope. A transect perpendicular to the coast was selected for sampling in estuary, inshore region, continental shelf and continental slope. Sampling was done in 16 stations in the depth range of 1.7–1000 m. The community structure was characterized in terms of species composition, abundance, diversity and feeding type. Four taxa were encountered in the study area comprising 181 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Cluster C1 included the samples from the ship-breaking area while the cluster C2 showed the grouping of the reference area. Sampling stations of different zones forming distinguished groups elucidate the alteration in species composition and abundance (Pravinkumar et al 2013;Khan et al 2017). However, similar to the nMDS analysis, CCA triplot also showed that all samples from the June accumulated on the same axis.…”
Section: Discussionmentioning
confidence: 57%
“…Cluster C1 included the samples from the ship-breaking area while the cluster C2 showed the grouping of the reference area. Sampling stations of different zones forming distinguished groups elucidate the alteration in species composition and abundance (Pravinkumar et al 2013;Khan et al 2017). However, similar to the nMDS analysis, CCA triplot also showed that all samples from the June accumulated on the same axis.…”
Section: Discussionmentioning
confidence: 57%
“…At the 200 m stratum, the relatively oxygenated (DO > 0.5 ml/l) sandy sediments of the Nicobar Islands harbored higher densities of crustaceans when compared to oxygen deficient (DO < 0.5 ml/l), sandy silt sediments of the Andaman Islands (Karakassis and Eleftheriou, 1997;Levin and Gage, 1998). The latter region was characterized by the dominance of polychaetes (91%), under the OMZ conditions (Abdul Joydas and Damodaran, 2014;Raman et al, 2015;Khan et al, 2017). Echinoderms, which are most vulnerable to oxygen depleted conditions (Diaz and Rosenberg, 1995;Parameswaran et al, 2018), were altogether absent in the oxygen deficient conditions prevailing at ∼200 m depth around the Andaman Islands.…”
Section: Macrozoobenthic Communitiesmentioning
confidence: 99%
“…dominated in these sites. The oligotrophic conditions around the ANI (Ansari and Abidi, 1989) resulted in low OM flux and retention in the sediments (0.05-3.90%), in contrast to the continuous OM deposition in other OMZ-impacted margins, which are usually associated with high productivity (Abdul Jaleel et al, 2014;Raman et al, 2015;Khan et al, 2017). This may be a factor resulting in lack of dominance in the study area, where the occurrence of diversified forms was better suited to utilize the available OM.…”
Section: Polychaete Diversity and Communitiesmentioning
confidence: 99%
“…Macroinvertebrate distributions are naturally patchy due to external influences and juvenile recruitment, as well as processes occurring within the already existing benthic assemblage (Underwood and Chapman 2005). Interactions between biotic and abiotic factors are complex (Khan et al 2017) and natural perturbations greatly contribute to spatial variations in populations (Underwood and Chapman 2005). Species have different tolerances to each abiotic variable, hence as the environment fluctuates, so does the corresponding community according to the preferences of its taxa (Gray and Elliott 2009).…”
Section: Environmental Influences On Macrobenthos Distributionmentioning
confidence: 99%
“…Polychaeta-dominance is common for coastal macrobenthic studies worldwide (Karakassis and Eleftheriou 1997, Ellingsen 2002, Shin et al 2004, Bigot et al 2006, Ellingsen et al 2007, Jayaraj et al 2007, Currie et al 2009, Raja et al 2014, and is also observed in fluviallydependent shelf ecosystems, such as on the south-east and west coasts of India (Jayaraj et al 2008, Joydas and Damodaran 2009, Khan et al 2017) and on the inner Brazilian shelf (Zalmon et al 2013). Jayaraj et al (2008) Although, even with the removal of sample 9B, overall diversity on the uThukela shelf was relatively high (H' = 2.90), ranging between 1.68 -3.85 at the sampled stations.…”
Section: Macroinvertebrate Community Structure On the Uthukela Shelfmentioning
confidence: 99%